Metabolic response of Brevibacterium epidermidis TRM83610 to NaCl stress - Luo, Tangliang; Zhao, Yafang; Wang, Lijun; Xia, Zhanfeng (Frontiers in Microbiology, 2026)
To elucidate the metabolic response of Brevibacterium epidermidis TRM83610 to NaCl stress and promote its industrial application, this study employed metabolomics techniques to analyze changes in intracellular metabolites—particularly compatible solutes—under NaCl concentrations of 0, 5, 10, and 15%. Response surface methodology was further applied to optimize key fermentation parameters including carbon and nitrogen source concentrations, composite salt concentration, pH, and temperature, in order to evaluate the strain’s ectoine production capacity. The results revealed significant metabolic differences among the salinity treatment groups, with various secondary metabolites associated with antimicrobial activity and plant growth promotion being detected. Six compatible solutes dominated by ectoine were identified, among which Nε-acetyl-L-lysine was reported for the first time in the genus Brevibacterium. The metabolic strategies adopted by the strain in response to NaCl stress included osmoadaptation, oxidative stress resistance, and competition for survival. Through response surface optimization, the ectoine titer reached 440.60 mg/L, representing a 6.22-fold increase over the initial yield of 70.75 mg/L and demonstrating considerable application potential. This study enriches the metabolic profile of B. epidermidis TRM83610, preliminarily reveals its metabolic adaptation mechanisms under NaCl stress, and provides a theoretical basis for its further development and utilization.